2009
DOI: 10.1016/j.otohns.2008.10.026
|View full text |Cite
|
Sign up to set email alerts
|

OK‐432 Sclerotherapy in Head and Neck Lymphangiomas: Long‐term follow‐up Result

Abstract: Initial and the long-term response rate were equally good for lymphangioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
8

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 11 publications
1
38
0
8
Order By: Relevance
“…3 Özellikle bleomisin ve picibanil (OK-432) enjeksiyonlarının yaygın kullanımı mevcuttur. Bleomisin antineoplastik etkisini DNA sentezini inhibe ederek gösteren anti-tümör bir ajandır ve yan etkisi oldukça azdır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…3 Özellikle bleomisin ve picibanil (OK-432) enjeksiyonlarının yaygın kullanımı mevcuttur. Bleomisin antineoplastik etkisini DNA sentezini inhibe ederek gösteren anti-tümör bir ajandır ve yan etkisi oldukça azdır.…”
Section: Discussionunclassified
“…Son yıllarda kullanılan yeni tedavi seçenekleri arasında öne çıkan bleomisin ve picibanil (OK-432) gibi sklerozan ajanların intralezyonel enjeksiyonları ile başarılı sonuçlar bildirilmektedir. 3 Özellikle bleomisin yaygın olarak kullanılmaktadır ve yan etkisi oldukça azdır. Lenfanjiyom ani solunum sıkıntısına yol açması yönüyle de önem taşımaktadır.…”
Section: Introductionunclassified
“…반복된 경화요 법 이후에 수술을 시행하는 경우에는 주변 조직과의 유착 및 출혈로 수술 중 어려움을 겪을 수 있다 [8]. 여기에서는 수술 적 치료를 우선적으로 시행하였던 두경부 림프관종의 경우 들에 대한 삼성서울병원의 사례를 살펴보고 수술 이후 현재 까지의 결과를 평가하였다.…”
Section: Journal Of Korean Association Of Pediatric Surgeonsunclassified
“…A regression of lymphangiomas after OK-432 therapy is reported in up to 96% of the patients. 9 Yoo et al 38 reported an initial response rate of 83.5% and long-term response rate of 76.3% after treatment with OK-432 of 55 patients with head and neck lymphangiomas.…”
Section: Ok-432mentioning
confidence: 99%